The Hematopoietic Potential of Tamarillo (Cyphomandra betacea) and Pitaya (Hylocereus spp.) Juices in Anemia Management: A Randomized Controlled Trial in Bukittinggi, West Sumatra, Indonesia - Nova H, Desri; Yeltra Armi; Mutia Felina; Zaharatul Hikmah; Riri Aprianti (Eureka Herba Indonesia, 2024)
Anemia is a global health concern, particularly prevalent in developing countries. Traditional remedies like tamarillo and pitaya have been suggested to boost blood production. This study aimed to evaluate the efficacy and safety of these juices in managing anemia. A randomized, double-blind, placebo-controlled trial was conducted in Bukittinggi, West Sumatra, Indonesia. Participants with mild to moderate anemia (hemoglobin 8-11 g/dL) were randomized to receive daily tamarillo juice, pitaya juice, or a placebo for 12 weeks. Hemoglobin, hematocrit, iron levels, and hematological parameters were assessed at baseline and week 12. A total of 150 participants completed the study (50 per group). Both tamarillo and pitaya juice groups showed significant increases in hemoglobin and hematocrit levels compared to the placebo group (p < 0.05). Pitaya juice also demonstrated a significant increase in iron levels (p < 0.01). No serious adverse events were reported. Tamarillo and pitaya juices show promise as adjunctive therapies for anemia management. Further research is needed to explore their long-term effects and mechanisms of action.